2021
DOI: 10.1155/2021/9936981
|View full text |Cite
|
Sign up to set email alerts
|

Manual Therapy as a Management of Cervical Radiculopathy: A Systematic Review

Abstract: Background. Cervical radiculopathy is defined as a disorder involving dysfunction of the cervical nerve roots characterised by pain radiating and/or loss of motor and sensory function towards the root affected. There is no consensus on a good definition of the term. In addition, the evidence regarding the effectiveness of manual therapy in radiculopathy is contradictory. Objective. To assess the effectiveness of manual therapy in improving pain, functional capacity, and range of motion in treating cervical rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…There are several mechanisms whereby the treatment provided in the present case could have led to a reduction in symptoms. We suggest that the cervical spine mobilizations may have alleviated radicular components of the patient’s neck pain, in accordance with a recent systematic review that found manual therapies were effective in reducing cervical radiculopathy [ 36 ]. However, this would only partially explain the improvement from her spectrum of symptoms (eg, not the broader pattern of neurologic deficits).…”
Section: Discussionsupporting
confidence: 86%
“…There are several mechanisms whereby the treatment provided in the present case could have led to a reduction in symptoms. We suggest that the cervical spine mobilizations may have alleviated radicular components of the patient’s neck pain, in accordance with a recent systematic review that found manual therapies were effective in reducing cervical radiculopathy [ 36 ]. However, this would only partially explain the improvement from her spectrum of symptoms (eg, not the broader pattern of neurologic deficits).…”
Section: Discussionsupporting
confidence: 86%
“…ND improves the mechanical function of nerve structures in terms of tension, sliding, and compression which can affect intraneural microcirculation. ND affects the mechanical function of peripheral nerves and changes in the mechanical function of these nerves have a direct impact on physiological changes in the nervous structure as of affecting the improvement of pain levels and functional abilities (Borrella-Andrés et al, 2021;Mayank Manojbhai Raval & Shweta Rameshbhai Rakholiya, 2022;Nugraha et al, 2019). This is also supported by a previous meta-analysis which stated that ND can reduce pain (mean difference, -1.89; 95% CI: -3.14, -0.64; p<0.001) in nerve-related neck and arm pain (Basson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…CSR incidence increases with age and has an estimated frequency of 0.35% in the fifth to sixth decade of life [ 2 ]. Recently, multiple systematic literature reviews have been published seeking to understand the complexities of CSM and its natural history, conservative management strategies, and the need for surgical interventions [ 2 , 8 , 9 , 10 , 11 , 12 , 13 ]. For patients with intractable pain and with motor loss of less than three out of five, surgical intervention is warranted [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with intractable pain and with motor loss of less than three out of five, surgical intervention is warranted [ 2 ]. However, in comparison between conservative and surgical management trials, the long-term outcomes at 1–2 years generally show conservative care to be equally effective for less severe CSM patients [ 2 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%